Spawning patterns and reproductive biology of yellowtail scad (Trachurus novaezelandiae) off south-eastern Australia - Stewart, John; Hegarty, Anne-Marie; Young, Caitlin; Gould, Antony; Craig, James (Frontiers in Fish Science, 2026)
We characterized the reproductive biology of the ecologically and commercially important small pelagic fish Trachurus novaezelandiae (yellowtail scad) in south-eastern Australian waters using a 25-year monitoring dataset. Sexual maturity occurred at 15.5 cm fork length (FL), with 95% of individuals mature by 23.2 cm FL. There were no significant differences in maturity ogives between sexes. Trachurus novaezelandiae exhibited an extended spawning season from July to March, peaking in October during the austral spring, consistent with sympatric small pelagic species in eastern Australian waters. Sex ratios in the commercial purse-seine fishery through 10 years were significantly skewed toward females (58%) and were consistent through years. Similarly to some other species within the Trachuridae, females predominated in all months except for those immediately following the spawning season, suggesting some differential sex-based availability to the fishery related to spawning. The fishery for T. novaezelandiae is currently classified as sustainable, with relatively low fishing mortality applied to the population. However, commercial harvests of small pelagic teleosts are rapidly increasing in Australian waters, and with developing markets it is likely that T. novaezelandiae will be fished more intensively in the future. The baseline information on reproductive biology in the present study may support sustainable exploitation through improved estimates of spawning stock biomass.